PENGARUH PEMBERIAN KREDIT TERHADAP PENINGKATAN PENDAPATAN USAHA KECIL DAN MENENGAH DI BANK BTPN MITRA USAHA RAKYAT PANDEGLANG (STUDI KASUS PADA NASABAH BANK BTPN MITRA USAHA RAKYAT PANDEGLANG) - Ipah Mulyani; Destiana (NIAGARA Scientific Journal, 2022)
This study aims to determine how big the influence of lending on the increase in income of small and medium enterprises at Bank BTPN Mitra Usaha Rakyat Pandeglang (Case Study on Customers of Bank BTPN Mitra Usaha Rakyat Pandeglang). The problem in this research concerns the insufficient amount of capital so that achieving fast business progress usually takes a long time. The research method used is quantitative associative. The population in this study were 92 customers who took credit at Bank BTPN Mitra Usaha Rakyat Pandeglang in 2020. The sampling technique used in this research is accidental sampling technique. Data analysis techniques used in this study include Validity Test, Descriptive Analysis, Correlation Coefficient Test, Coefficient of Determination Test and t Test. The results of the calculation show that there is a moderate effect between the provision of credit on increasing income with a correlation of 0.480. The coefficient of determination of 0.231 or 23.1% means that it shows that the variable of credit has an effect of 23.1% on the increase in income, the remaining 76.9% is influenced by other factors not explained by the researcher. The results of the hypothesis test show that the tcount > t-table is 5.196 > 1.66196. So the value of t-count is greater than t-table thus Ha is accepted and Ho is rejected. The test results show that there is a significant effect between lending to increasing income.